Tax Avoidance, Ownership, Commissioners, And Debt Costs: The Role of Transparency - Aurel Ariandrani Bilqiis; Sari Rahmadhani (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study investigates the effects of tax avoidance, institutional ownership, and independent commissioners on debt costs, with transparency serving as a moderating variable. The research sample consists of consumer cyclical sector companies listed on the IDX from 2021 to 2023. Samples were selected using a purposive sampling method, resulting in 84 companies. The study applies multiple linear regression analysis and moderated regression analysis. The results show that tax avoidance hurts the cost of debt. Institutional ownership also negatively impacts the cost of debt, while independent commissioners have a positive effect. Additionally, transparency does not moderate the relationship between tax avoidance and debt costs, nor does it moderate the link between institutional ownership and debt costs. However, transparency can reduce the negative impact of independent commissioners on the cost of debt.